2015
DOI: 10.18632/oncotarget.3893
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated mutant strain of Salmonella Typhimurium lacking the ZnuABC transporter contrasts tumor growth promoting anti-cancer immune response

Abstract: Salmonella Typhimurium has been shown to be highly effective as antitumor agent. The aim of this study was to investigate the tumor targeting efficacy and the mechanism of action of a specific attenuated mutant strain of Salmonella Typhimurium (STM) devoid of the whole operon coding for the high-affinity zinc transporter ZnuABC, which is required for bacterial growth in environments poor in zinc and for conferring full virulence to different Gram-negative pathogens.We showed that STM is able to penetrate and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…This might, at least in part, accounted for the good antitumor effects produced by MWA combined with VNP 20009 therapy. Moreover, it was reported that bacteria treatment could stimulate a specific immune pattern and a potent inflammatory response, which could induce tumor-specific immune responses and contrast the immunosuppressive environment generated by tumors [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might, at least in part, accounted for the good antitumor effects produced by MWA combined with VNP 20009 therapy. Moreover, it was reported that bacteria treatment could stimulate a specific immune pattern and a potent inflammatory response, which could induce tumor-specific immune responses and contrast the immunosuppressive environment generated by tumors [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that leu-arg auxotrophic S. enterica strain (A1-R) can effectively inhibit and in some cases even eradicate different types of primary and metastatic tumors when used as monotherapy in mouse models of prostate cancer [33-35], breast cancer [36][37][38], lung cancer [39,40], ovarian cancer [41,42], cervical cancer [43], pancreatic cancer [44][45][46][47][48], sarcoma [49][50][51] and glioma [52,53]. Recently, researchers have demonstrated that the S. enterica Typhimurium strain (STM) deficient for a zinc transporter operon can invade and proliferate in tumor cells, exerting therapeutic effect in the mammary adenocarcinoma mouse model by promoting an antitumor immune response [54]. Evaluation of VNP20009, an attenuated S. enterica Typhimurium strain (msbB -and purA -), against many types of tumors [7,28] has shown that this strain provided good results in animal models, but it failed in terms of tumor colonization efficacy and antitumor activity in human patients during Phase I clinical trials [21].…”
Section: Discussionmentioning
confidence: 99%
“…This antitumor activity is partly explained by oncolytic mechanisms that are activated because of bacterial incorporation into the tumor microenvironment. Some of these mechanisms ( Figure 1 ) are (1) competition for tumor cell nutrients [ 12 ]; (2) release of antitumor bacterial components due to lysis of the bacteria adhered to the tumor cell [ 34 ], such as Salmonella enterica nitrate reductase that metabolizes nitrates and nitrites [ 35 ], products of the hypoxic tumor environment [ 36 ] into nitric oxide (NO) [ 18 ], which has the ability to induce tumor cell apoptosis [ 37 ]; (3) decreased angiogenesis due to inhibition of the transcription factor HIF-1 α and VEGF [ 38 ]; (4) activation of autophagy due to decreased phosphorylation of the proteins AKT and mTOR and increasing proteins as Beclin-1 and LC3 (microtubule-associated protein 1A/1B-light chain 3) [ 39 , 40 ]; and (5) increased amounts of calreticulin [ 41 ], a protein associated to immunogenic cell death that is currently being evaluated as a possible therapeutic alternative in cancer [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that some of the mechanisms that could use the bacterium to eliminate the tumor cells once it is in the tumor microenvironment involved enhance the expression of soluble mediators such as inducible nitric oxide synthase (iNOS) and interferon Îł (IFN- Îł ) and also inhibit the expression of immunosuppressive factors such as arginase-1, interleukin-4 (IL-4), transforming growth factor- ÎČ (TGF- ÎČ ), and vascular endothelial growth factor (VEGF) [ 19 ] ( Figure 2(a) ). In addition, Salmonella enterica also can decrease the activity of myeloid-derived suppressor cells (MDSCs) within the tumor microenvironment [ 76 ] and promotes the recruitment of NK cells [ 77 ], neutrophils [ 18 ], macrophages [ 19 ], and T [ 21 ] and B lymphocytes [ 20 ] into the tumor microenvironment and spleen [ 41 ].…”
Section: Introductionmentioning
confidence: 99%